Sputum quality assessment regarding sputum culture for diagnosing lower respiratory tract infections in children. - Popova, Gorica; Boshkovska, Katerina; Arnaudova Danevska, Ivana; Spasova Smilevska, Olga; Jakjovska, Tatjana (ID Design Press,Skopje, Republic of Macedonia, 2019)
BACKGROUND:The clinical relevance of specimens from the lower airways is often debatable. However, they are most commonly examined for diagnosing lower respiratory tract infections (LRTIs).AIM:This study aimedto determine the diagnostic value of sputum quality assessment aboutsputum culture for diagnosing LRTIs in children.METHODS:In six months, a total of 1485 sputum samples were quality assessed by using Bartlett’s grading system. All samples, regardless of their quality, were cultured, identified, and antimicrobial susceptibility testing was performed by Kirby-Bauer disc-diffusion method.RESULTS:Among the acceptable category, defined by Bartlett’s grading system, 132 (63.2%) samples showed culture positivity of which Streptococcus pneumoniae48 (36.4%) was most commonly isolated, followed by Moraxella catarrhalis22 (16.7%) and Haemophilus influenza21 (15.9%). Among the non-acceptable category, 185 (14.5%) samples were culture positive of which most commonly isolated were Escherichia coli, Staphylococcus aureusand Pseudomonas aeruginosawith 64 (34.6%), 54 (29.2%) and 28 (15.1%), respectively.CONCLUSION:Sputum quality assessment is a useful tool for distinguishing the true respiratory pathogens from possible colonising flora for which antibiotic treatment should not be highly considered.
Keywords: Sputum culture; Quality assessment; Streptococcus pneumoniae; Escherichia coli